The future of asylum in the European Union problems, proposals and human rights - Goudappel, Flora A. N. J.; Raulus, Helena S. (T. M. C. Asser Press, 2011)
This book is the updated result of a conference on the future of the European asylum policy at Erasmus School of Law in Rotterdam, the Netherlands. After a challenge set by the Dutch State Secretary for Justice, Ms. Nebahat Albayrak, the contributions to this book focus on human rights aspects of the European asylum policy and the way the EU Member States need to cooperate in the future in order to reach results. The authors are scholars, policy makers and representatives of NGOs. In this way, many different aspects of the problems are put forward and conflicting views on the evaluation of the EU asylum issues come to light.This book is highly recommended to academics, practitioners, policymakers and NGOs involved in European asylum policy issues.